In vitro antimicrobial, anticancer and antioxidant activities and bioactive contents of endemic Acanthus dioscoridis L. var. dioscoridis flowers from Türkiye - Keser, Serhat; Kaygılı, Omer; Tekin, Suat; Türkoğlu, İsmail; Yılmaz, Prof. Dr. Ökkeş; Karatepe, Mustafa; Sandal, Süleyman (Niyazi BULUT, 2024)
A. dioscoridis is a member of the Acanthaceae family and is represented by approximately 30 species. In Türkiye, 8 species, 6 of which are endemic, are distributed in Eastern and Central Anatolia. In the presented study, the antimicrobial, antiradical, and anticancer properties of flower extracts of endemic A. dioscoridis L. var. dioscoridis were investigated for the first time. The antiradical activity and phytochemical contents of this plant were also investigated. According to our study results, endemic A. dioscoridis flowers extract show anticancer activity against MCF-7, HCT-116 and LNCaP cancer cell lines, high antiradical activity against ABTS radicals, and effective antimicrobial activity against some microorganism-caused infection in humans. In conclusion, this study can be the first report about the anticancer, antiradical, and antimicrobial properties of endemic A. dioscoridis L. var. dioscoridis flower extracts.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)